Efficiency in index options markets and trading in stock baskets - Lucy F. Ackert; Yisong S. Tian (Federal Reserve Bank of Atlanta, 1999)
Researchers have reported mispricing in index options markets. This study further examines the efficiency of the S&P 500 index options market by testing theoretical pricing relationships implied by no-arbitrage conditions. The effect of a traded stock basket, Standard and Poor's Depository Receipts (SPDRs), on the link between index and options markets is also examined. Pricing efficiency within options markets improves, and the evidence supports the hypothesis that a stock basket enhances the connection between markets. However, when transactions costs and short sales constraints are included, very few violations of the pricing relationships are reported.
Keywords: 330; Options (Finance); Stock - Prices